2017
DOI: 10.29220/csam.2017.24.6.583
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics for the Cox model

Abstract: The most popular regression model for the analysis of time-to-event data is the Cox proportional hazards model. While the model specifies a parametric relationship between the hazard function and the predictor variables, there is no specification regarding the form of the baseline hazard function. A critical assumption of the Cox model, however, is the proportional hazards assumption: when the predictor variables do not vary over time, the hazard ratio comparing any two observations is constant with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 83 publications
(96 reference statements)
0
30
0
Order By: Relevance
“…It assumes proportional hazards, an assumption that relative risks, such as male vs female, are constant over time. The proportional hazards assumption of the Cox regression model was assessed by chi‐square tests of Schoenfeld residuals …”
Section: Methodsmentioning
confidence: 99%
“…It assumes proportional hazards, an assumption that relative risks, such as male vs female, are constant over time. The proportional hazards assumption of the Cox regression model was assessed by chi‐square tests of Schoenfeld residuals …”
Section: Methodsmentioning
confidence: 99%
“…Common choices of g(t) include the Kaplan‐Meier (KM) transformation, which scales the horizontal axis by the left‐continuous version of the KM survival curve, the identity function, and the natural logarithm function. Formulation is rather general, as many tests fall within this framework for different choices of g(t) (see, eg, Xue and Schifano, ). Writing in matrix notation yields λi(t)=λ0(t)exp [Xi(t){bold-italicβ+bold-italicG(t)bold-italicθ}],1emi=1,,n, where bold-italicG(t) is a p×p diagonal matrix with the j th diagonal element being gj(t), and bold-italicθ=(θ1,,θp).…”
Section: Cox Ph Modelmentioning
confidence: 99%
“…The online updating cumulative statistic Tk(G) was calculated to be 95.60. Due to the relatively high censoring rate, the KM transformation was chosen for calculation of the diagnostic statistics as it is more robust in such a scenario (eg, Xue and Schifano, ). Diagnosis with function plot.cox.zph() in the survival package revealed that all the parameters are likely to be time‐dependent; see Figure S5.…”
Section: Survival Analysis Of Seer Lymphoma Patientsmentioning
confidence: 99%
See 2 more Smart Citations